The Effectiveness of The Blended Learning Method as A Learning Innovation During The Covid-19 Pandemic at Faculty Of Dentistry, Hang Tuah University Surabaya - Nora Lelyana; Aulia Dwi Maharani; Ghita Hadi Hollanda (Denta Journal Kedokteran Gigi, 2024)
Background: The covid-19 pandemic has an impact on many sectors include the education sector. Dental education students are not only given academic knowledge but also need to be trained for their dental practice skills. Various obstacles during covid-19 pandemic require educational institutions to make innovations to maintain the quality of graduates. One of the innovations that can be implemented is blended learning. Blended learning combines online methods for lecture substitution and face-to-face methods for clinical activities on phantoms. The indicator of success of this method is by getting pass in the National Competency Exam for Dentist (UKMP2DG).  Objective: To determine the effectiveness of the blended learning method as a learning innovation during the covid 19 pandemic at the Faculty of Dentistry, Hang Tuah University Surabaya. Methods: This is an observational analytic study by comparing the percentage of UKMP2DG’s passing rates during the period before the covid 19 pandemic (2019) and during the implementation of the blended learning method (2021 and 2022). Data analysed using one-way Anova with an error of 5%. Results: The results of oneway Anova showed p value = 0.120> 0.05. Conclusion: There is no significant difference between the number of UKMP2DG passing rates from 2019, 2021 and 2022 means blended learning method can provide the same number of pass rate as other previous methods.